Personalization of Art Students' Training in the Context of the Transition to the Digital Economy - V. Mishina, Anastasia; I. Batyrshina, Gulnara; M. Yavgildina, Zilia; S. Avramkova, Irina (International Journal of Criminology and Sociology, 2022)
Today, one of the main resources for the effective functioning of many political, sociocultural, and communication processes is transition to the digital economy and digital reality in general. Informatization, computerization, automation naturally integrate into the artistic culture and transform it into a digital one. As a result, changes in the professional field of art definitely require changes in both the content, methodology and technological base of art education in the context of transition to digital economy. At the same time, digital technologies are a factor in the modernization of the higher education system, and its tool. There is an objective need to individualize and personalize educational technologies. In turn, digitalization creates the foundations by which these processes can be implemented. The article specifies pedagogical conditions for personalization of art students' training: activating self-education and self-development mechanisms through the creation of individual educational routes; enriching the informational educational and methodological base to maintain an individual format for studying the content of artistic culture; adopting a personal position of an adviser and a facilitator by the university teacher, which contributes to the design, stimulation and reflection of the personal and competent development of art students. The reliability of conclusions made within this theoretical study is confirmed by the positive results of experimental work.